2018
DOI: 10.3174/ajnr.a5898
|View full text |Cite
|
Sign up to set email alerts
|

Value of BRAF V600E in High-Risk Thyroid Nodules with Benign Cytology Results

et al.

Abstract: BACKGROUND AND PURPOSE: Limitations of ultrasound-guided fine-needle aspiration include nondiagnostic, indeterminate cytology and false-negative results. The BRAF V600E mutation is a specific biomarker for papillary thyroid carcinoma. This study aimed to investigate the additional diagnostic role of the BRAF V600E mutation in high-risk thyroid nodules with benign cytology results. MATERIALS AND METHODS: A total of 787 high-risk nodules in 720 patients underwent ultrasound-fine-needle aspiration. A subsequent B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The sensitivity of BRAF V600E mutation analysis has been proven to be so high for PTC, that even if benign cytology with positive BRAF V600E mutation were reported, more aggressive management should still be considered [ 52 ]. Consequently, some authors recommend, that fine-needle aspiration should be routinely accompanied by the BRAF V600E mutation test in high-risk thyroid nodules with ≥2 suspicious ultrasound features [ 53 ]. As postulated by Zhang et al [ 37 ], EU-TIRADS could be used as the preliminary evaluation method to select high-risk lesions for FNAB, while BSRTC and BRAF V600E mutation analysis should be adopted to refine the diagnosis, as an increased level of EU-TIRADS classification was significantly associated with the rising mutation rate of BRAF V600E in each BSRTC category.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of BRAF V600E mutation analysis has been proven to be so high for PTC, that even if benign cytology with positive BRAF V600E mutation were reported, more aggressive management should still be considered [ 52 ]. Consequently, some authors recommend, that fine-needle aspiration should be routinely accompanied by the BRAF V600E mutation test in high-risk thyroid nodules with ≥2 suspicious ultrasound features [ 53 ]. As postulated by Zhang et al [ 37 ], EU-TIRADS could be used as the preliminary evaluation method to select high-risk lesions for FNAB, while BSRTC and BRAF V600E mutation analysis should be adopted to refine the diagnosis, as an increased level of EU-TIRADS classification was significantly associated with the rising mutation rate of BRAF V600E in each BSRTC category.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported six false-positive results in 126 specimens and, among them, BRAF V600E was also detected by using pyrosequencing in four cases [17]. Chen et al reported five false-positive results in 292 specimens [18]. RET/PTC was also highly predictive for PTC (100%) and classic PTC (>82%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the number of suspicious US features can predict the malignancy of thyroid nodules that had benign FNA results but were pathologically proven to be malignant [28]. In our research, suspicious US features with unde ned boundary and microcalci cation can be suggestive of malignancy, therefore BRAF V600E gene detection is necessary for these thyroid nodules with above malignant features, even if the cytological results were benign.…”
Section: Discussionmentioning
confidence: 63%